Construction technology - Chudley, R.; Greeno, Roger; Hurst, Mike; Topliss, Simon (Pearson Education Limited, 2011)
'Construction Technology' provides a comprehensive introduction to every aspect of the technology of domestic low-rise construction and principal associated legislation